Strategi Komunikasi Pemasaran Terpadu Hotel Labersa Balige - Liyushiana Liyushiana (Tourism, Hospitality And Culture Insights Journal, 2022)
Labersa hotel and convention center is a hotel located in Toba Regency, Balige District, which is a new hotel but can increase visitors from time to time. But for now, the interest of visitors to stay at Balige, especially to the location of the Labersa Hotel, has not yet reached the expected target. To deal with this problem, an integrated and targeted communication strategy is needed. This scientific article discusses how to implement the concept of integrated marketing communication created by Philip Kotler and then we apply it using qualitative research methods. The results of this analysis show that applying this concept can overcome the existing problems. This research will be conducted using descriptive qualitative research and data collection methods using observation, interviews, and documentation of the hotel.